AT A CROSSROADS: FIGHT-OR-FLIGHT FOR WOMEN INTERIOR DESIGNERS IN CONSTRUCTION - Shaharudin, N.; Noorhani, N. M. A.; Mustapha, A. A.; Anuar, F. N. K.; Mustafa, N. K. F. (Journal of Engineering and Technology (JET), 2025)
This study investigates the challenges experienced by women in the male-dominated construction sector, focusing on the interior design field. While female participation in various professional fields is rising, there remains a notable gap in research addressing the unique barriers that female interior designers face. These barriers include navigating gender discrimination, confronting negative societal perceptions, limited project management skills and knowledge, difficulty achieving work-life balance, restricted career growth opportunities, lack of mentorship and unsupportive working environments. This qualitative research utilizes a survey with open-ended questions as its primary instrument, targeting 150 female interior designers randomly selected from the Malaysian Institute of Interior Designers (MIID) membership list. Data were analysed through thematic content analysis to identify key themes and patterns. Out of the 150 participants, only 113 completed the survey with 94 respondents acknowledging experiences of gender bias, underscoring women’s underrepresentation in this sector. The most critical challenge identified was the limited project management skills and knowledge, which not only restricts career advancement but also intensifies the struggle for women to assert their roles in the industry. Findings from this study emphasize the urgent need for targeted initiatives to develop these skills and promotes a more inclusive environment for female interior designers within the construction industry.